Specifics of state control in the financial and the social sphere - E. I. Kuznetsova (Путеводитель предпринимателя)
The article discusses the concept of system management at the state level, its properties, functions. Special attention is paid to social control as self-governed and dynamic system and management in the financial sector as the most important for the development of the economy and its control.